Chapter 18 Didactics and Innovation in Collaboration for the Unforeseen in Training Practice Preparation - Magnussen, Leif (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The objective of this chapter is to improve collaborative practices and exercises, taking the unforeseen into account. The major focus is on the process of making collaboration exercises and the planning phase of these potential learning situations. Two educational perspectives will be explored in order to improve the planning work itself and, possibly, also training for the unforeseen. The use of social technology, together with didactic thinking, may enhance the extent and quality of collaboration training. Planners also need to deliberate upon the importance of "standard" or traditional exercises in combination with collaboration, seeing the whole picture and the exercise as a program. On the other hand, it is of vital importance to train in the realms of the unforeseen, entering the uncharted waters of learning outside known territory."